1974
DOI: 10.1002/art.1780170212
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary criteria for the classification of systemic lupus erythematosus (SLE) evaluation in early diagnosed SLE and rheumatoid arthritis

Abstract: Preliminary criteria for the classification of systemic lupus erythematosus (SLE) were applied to patients with early diagnosed SLE and rheumatoid arthritis (RA) who are participants in a prospective community study of arthritis of recent onset. Sensitivity of the criteria was 88 % , and specificity against RA was 97.5 ye. Sensitivity increased to 92 % without loss of specificity when high titer antinuclear antibody (ANA) was used as an alternative criteria manifestation to LE cells. These results show the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…A positive ANA was used in place of a positive LE cell preparation by Fries and Siege1 (12) and by Trimble et a1 (13), who thus did not test the preliminary criteria as defined. Criticisms were directed at the vague wording of some criteria, e.g., Raynaud's phenomenon, hemolytic anemia, convulsions, and psychosis (9), the type ("classic" nature) of and predominant features of the population tested (12), and the low sensitivity of the LE preparation versus the sensitivity of ANA (13). In the formulation of the 1982 revised criteria, ANA, anti-DNA, and anti-Sm were included while alopecia and Raynaud's phenomenon were dropped for lack of acceptable specificity.…”
Section: Discussionmentioning
confidence: 99%
“…A positive ANA was used in place of a positive LE cell preparation by Fries and Siege1 (12) and by Trimble et a1 (13), who thus did not test the preliminary criteria as defined. Criticisms were directed at the vague wording of some criteria, e.g., Raynaud's phenomenon, hemolytic anemia, convulsions, and psychosis (9), the type ("classic" nature) of and predominant features of the population tested (12), and the low sensitivity of the LE preparation versus the sensitivity of ANA (13). In the formulation of the 1982 revised criteria, ANA, anti-DNA, and anti-Sm were included while alopecia and Raynaud's phenomenon were dropped for lack of acceptable specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the incidence of the various ARA criteria descriptives in the current series with those from whom the criteria were devcloped (4) and a subsequent followup study (29) revealed similar frequencies with two exceptions.…”
Section: Resultsmentioning
confidence: 61%
“…The immune-complex disease of our patient is close to the symptomatol ogy described in necrotizing vasculitis occurring in systemic lupus erythe matosus [TuffaneUi and Kay, 1969], In fact, according to the American Rheu matism Association, systemic lupus erythematosus is characterized by 14 criteria [Cohen and Canoso, 1972] and antinuclear antibodies are associated with 3 other signs in 92% of these patients [Trimble et al, 1974], In our patient, vasculitis is present with four of these major clinical and serological signs, namely: butterfly facial erythema, arthritis, leukopenia and antinuclear antibodies at a titer higher than 1/64. More precisely, this affection corre sponds to the so-called drug-induced lupus syndrome which differs from systemic lupus erythematosus in that it rarely involves kidneys, displays normal complement level with absence of anti-DNA antibodies and improves after withdrawal of the nociceptive drug [Harpey et a/., 1972;Blombren et al, 1972;Utsinger et al, 1976].…”
Section: Discussionmentioning
confidence: 94%